Accommodation of lattice mismatch in a thiol self-assembled monolayer - She, Zhe; Lahaye, Dorothée; Champness, Neil R.; Bühl, Michael; Hamoudi, Hicham; Zharnikov, Michael; Buck, Manfred (The journal of physical chemistry. C, Energy, materials, and catalysis, 2013)
The structure of self-assembled monolayers (SAMs) of 3-(4′-(methylthio)-[1,1′-biphenyl]-4-yl)propane-1-thiol (CH3S(C6H4)2(CH2)3SH) formed on Au(111)/mica has been investigated by scanning tunneling microscopy (STM), high-resolution X-ray photoemission spectroscopy (HRXPS), near-edge X-ray absorption fine structure (NEXAFS) spectroscopy, and density functional theory (DFT) calculations. A highly crystalline monolayer terminated by thioether moieties is formed, which adopts a structure that differs from the previously studied CH3 terminated analogue with its 2√3 × √3 unit cell. An oblique 2√3 × √61 chiral unit cell containing 8 molecules is proposed. Accommodation of the substantial mismatch between the lattices of the SAM and substrate is explained by molecular design. Serving as a buffer layer, the alkane spacer decouples the SAM lattice, defined by the functionalized aromatic moieties, from the substrate.
Published: February 4, 2013
Gesehen am 24.01.2022